Synergistic effect of arbuscular mycorrhizae and Trichoderma sp. on growth, nutrient uptake and yield of Phaseolus mungo l. cultivars - Sharma, Navnita (2021)
This study compared the response of two Phaseolus mungo L. cultivars, UH-1 and IPU-94-1, to arbuscular mycorrhizal fungi (AMF) and Trichoderma viride in combination or alone in pot culture under green house conditions. After 120 days of inoculation, plants were analysed for different growth parameters and it was found that inoculation of Glomus mosseae, Acaulospora laevis and T. viride followed by dual inoculation of G. mosseae and T. viride in both varieties stimulated growth parameters, phosphatase activity, nutrient uptake and yield. Better plant response to the different treatments was exhibited by variety UH-1 as compared to IPU-94-1 but variety IPU-94-1 responded better than UH-1 for increasing fresh and dry shoot weight, fresh root weight, and acidic phosphatase activity when both the varieties were treated with A. laevis. Among the two mycorrhizal fungi used, G. mosseae proved to be better bioinoculant compared to A. laevis for improving growth in both the cultivars.